COMPARISON OF ULTRASOUND GUIDED ERECTOR SPINAE PLANE BLOCK AND LOCAL SKIN INFILTRATION FOR POSTOPERATIVE ANALGESIA IN ADULT PATIENTS UNDERGOING LUMBAR SPINE SURGERY UNDER GENERAL ANAESTHESIA - MITTAL, MANSI; KAUR, CHANDANDEEP (International Journal of Current Pharmaceutical Research, 2026)
Objective: To compare the efficacy of ultrasound-guided Erector Spinae Plane (ESP) block with local skin infiltration for postoperative analgesia in adult patients undergoing lumbar spine surgery under general anaesthesia. Methods: Sixty ASA I-II patients aged 18-80 y undergoing elective lumbar spine surgery were randomized into two groups of 30 each. Group E received ultrasound-guided bilateral ESP block with 0.25% Bupivacaine 10 ml on each side (total 20 ml), while Group l received local skin infiltration with 20 ml of 0.25% Bupivacaine. Visual Analogue Scale (VAS) scores, time to first rescue analgesia, hemodynamic parameters (heart rate, blood pressure, mean arterial pressure, SpO2), and adverse effects were assessed at 15 min, 30 min, 1 h, 1.5 h, 2 h, 4 h, and 6 h postoperatively. Results: Group E demonstrated significantly lower VAS scores at all time intervals compared to Group l (p<0.05). The time to first rescue analgesia was significantly prolonged in Group E (1.95±0.48 h) compared to Group l (1.63±0.43 h, p=0.01). Group E showed better hemodynamic stability with significantly lower pulse rate and mean arterial pressure at 6 h (p<0.05). SpO2 was significantly higher in Group E at 15 min, 30 min, 2 h, and 4 h (p<0.05). No adverse effects were observed in either group. Conclusion: Ultrasound-guided erector spinae plane (ESP) block provides superior postoperative analgesia, prolongs the time required for rescue analgesia, reduces opioid consumption, and maintains better hemodynamic stability compared to local skin infiltration in patients undergoing lumbar spine surgery.